Gum Arabic-enhanced magnetic biochar nanophotocatalyst for efficient metronidazole degradation in wastewater - Majid Amiri Gharaghani; Khadijeh Azarshab; Fateme Ameli; Mohammad Ansarizadeh; Mohammad Reza Samaei; Alireza Nasiri; Hakimeh Mahdizadeh; Hassan Hashemi; Amin Mohammadpour (Results in Engineering)
In this study, a novel magnetic nanocomposite based on biochar and Gum Arabic (GA) was synthesized using a microwave-assisted co-precipitation method. As a natural polysaccharide, Gum Arabic played a multifaceted role in enhancing the physical, chemical, and surface stability properties of the nanoparticles. The resulting nanocomposite exhibited favorable magnetic characteristics and high catalytic activity, which were attributed to the presence of iron (Fe), cobalt (Co), and copper (Cu) within its nanoscale structure. Under optimal conditions, including a catalyst dosage of 0.2 g/L, an initial pH of 7.5, and an initial metronidazole (MNZ) concentration of 10 mg/L, under 50 min of UV-C irradiation, the removal efficiency of MNZ reached 95.45% in simulated aqueous environments and 75% in real wastewater samples. Kinetic studies revealed that the degradation process followed a pseudo-first-order kinetic model. Additionally, the mineralization rate reached 69.56% after 50 min of irradiation. Investigations into the effect of oxidizing agents demonstrated that persulfate exhibited superior performance compared to other oxidants, with hydroxyl radicals playing a key role in the oxidation process. The nanocomposite showed good stability during recovery and reuse cycles, indicating its potential for multiple applications. These findings suggest that the Gum Arabic-based nanocomposite can serve as an effective catalyst for the environmental remediation of pollutants such as metronidazole.